Perception of EFL Students in Different Degree on Using Artificial Intelligence (AI) As English Learning Tools (Conference on English Language Teaching, 2025)
One of the effects of the rapid development of technology is the emergence of new technological innovations, one of them is Artificial Intelligence (AI), the benefits of AI are already widely used in various fields, including the economy, government, socio-culture, and education. Therefore, this study aimed to investigate perception of EFL students in different degree on using AI as English learning tools. This study employed by quantitative descriptive method that involving 33 students in different degree as the participations. The data were collected by using questionnaire and interview. The results of the study showed that the EFL students have positive perceptions of using Artificial Intelligence (AI) as their learning tools to learn English. The most AI they used is chat Gbt, the others are duolinggo, memrise, grammarly, elsa speak, meta-AI, gemini, deepL Translation, claude AI,etc. They used AI for doing homework or assignment, translating, enriching vocabulary, improving English skills, learning grammar, etc. The results also showed that students get the benefits from using AI, making learning more interesting and enjoyable, enriching vocabulary, improving English skills, and better understanding in grammar.